2001
DOI: 10.1002/cne.10074
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal organization of the melanin‐concentrating hormone system in primitive actinopterygians: Evolutionary changes leading to teleosts

Abstract: Hypothalamic melanin-concentrating hormone (MCH) neurones occur in all vertebrates and have an apparent neuromodulatory role. In teleost fish, however, MCH is used also as a neurohypophysial hormone, controlling skin color, and as a hypophysiotrophic peptide. This work describes the central location of immunoreactive MCH perikarya and their projections to the pituitary in a range of ancestral fish to determine the phylogenetic stage when the peptide adopted these roles. In all actinopterygians examined, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 51 publications
2
58
0
Order By: Relevance
“…Similar MCH-mRNA-expressing cell clusters have been previously reported in several teleost species including rainbow trout [35], cichlid fish, Cichlasoma dimerus [7], tilapia [4], barfin flounder [6] gilthead seabream [5] and eel [36]. Hypothalamic-hypophyseal neurons in the lateral tuberal nucleus respond strikingly to background color changes and constitute the most prominent MCH-mRNA-expressing cell cluster in the teleost brain [36]. Most of the axons of the MCH-producing cells from the lateral tuberal nucleus project to the pituitary [37] but studies in several species including goldfish have further reported dense MCH innervation within all main brain regions [34].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…Similar MCH-mRNA-expressing cell clusters have been previously reported in several teleost species including rainbow trout [35], cichlid fish, Cichlasoma dimerus [7], tilapia [4], barfin flounder [6] gilthead seabream [5] and eel [36]. Hypothalamic-hypophyseal neurons in the lateral tuberal nucleus respond strikingly to background color changes and constitute the most prominent MCH-mRNA-expressing cell cluster in the teleost brain [36]. Most of the axons of the MCH-producing cells from the lateral tuberal nucleus project to the pituitary [37] but studies in several species including goldfish have further reported dense MCH innervation within all main brain regions [34].…”
Section: Discussionmentioning
confidence: 61%
“…However, the latter study did not describe the presence of MCH-producing cells associated to the PVO within the caudal hypothalamus but immunoreactive cell bodies were reported within the zona limitans. Similar MCH-mRNA-expressing cell clusters have been previously reported in several teleost species including rainbow trout [35], cichlid fish, Cichlasoma dimerus [7], tilapia [4], barfin flounder [6] gilthead seabream [5] and eel [36]. Hypothalamic-hypophyseal neurons in the lateral tuberal nucleus respond strikingly to background color changes and constitute the most prominent MCH-mRNA-expressing cell cluster in the teleost brain [36].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In mammals, mchr1 transcripts are distributed wider than mchr2 transcript (Boutin et al 2002;Schlumberger et al 2002;Eberle et al 2004). The wide distribution of mchr2 transcripts in peripherals coincides with the role of MCH as a neurohypophysial hormone as shown by extensive projections of the neuron from the hypothalamus to PN in ray-finned fish including barfin flounder (Naito et al 1985;Batten and Baker 1988;Minth et al 1989;Mancera and Fernández-Llebrez 1995;Baker and Bird 2002;Amano et al 2003).…”
Section: Distribution Of Gene Transcriptsmentioning
confidence: 81%